TEORI BELAJAR HUMANISTIK ABRAHAM MASLOW DAN CARL ROGERS SERTA IMPLIKASINYA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Insani, Farah Dina (AS-SALAM, 2019)
This article aims to describe the humanistic learning theory and its implications for learning Islamic Religious Education. Collecting research data using the documentation method, whether in technique, data in library research (library research). The object of study is an article that focuses on Abraham Maslow and Carl Rogers' Humanistic learning theory and its implementation in Islamic Education learning. The results of this study indicate that humanistic learning theory is a learning process that originates and ends in humans, everything rests on human values. The humanistic education system approach emphasizes the development of human dignity who makes choices and has beliefs. Learning is considered significant, if the learning material has relevance to student needs. Students who act as the main actors interpret the process of their own learning experience. The expected positive impact of this article is the appreciation of the wider community about the importance of humanizing humans in learning activities to achieve self-actualization of students.